2021
DOI: 10.1186/s12904-021-00775-6
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care preferences among cancer patients in Southern Thailand: a university hospital-based cross-sectional survey

Abstract: Background End-of-life care preferences may be highly individual, heterogenic, and variable according to culture and belief. This study aimed to explore preferences and factors associated with end-of-life care among Thai cancer patients. Its findings could help optimize the quality of life of palliative cancer patients. Methods A cross-sectional study surveyed palliative cancer outpatients at Songklanagarind Hospital from August to November 2020. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Moreover, the top 3 most important components regarding EoL care wishes were: receiving the full truth about their illnesses, not being a burden to the family, and participating or performing in religious rituals. These findings were concordant with earlier reports from the USA [ 23 ] together with a study regarding Thai elderly people [ 12 ], and Thai palliative cancer patients [ 14 ]. A reason for this may be due to most participants in this study being older adults with a mean age of 54 years.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, the top 3 most important components regarding EoL care wishes were: receiving the full truth about their illnesses, not being a burden to the family, and participating or performing in religious rituals. These findings were concordant with earlier reports from the USA [ 23 ] together with a study regarding Thai elderly people [ 12 ], and Thai palliative cancer patients [ 14 ]. A reason for this may be due to most participants in this study being older adults with a mean age of 54 years.…”
Section: Discussionsupporting
confidence: 93%
“…This issue might be a universal need among all people and patients in regards to quality of life when receiving EoL care. Moreover, this finding was similar to a prior study among Thai palliative cancer patients [ 14 ] highlighting that pain management was still an unsolved issue needing more attention from physicians tasked with identifying and alleviating pain and other distressing symptoms [ 26 ]. Therefore, patients’ anxiety about the management of their suffering, by the healthcare system, during their EoL period should be tackled.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Patients' perceptions of the dignity and meaning of life can help them prepare for death [16]. Pitanupong et al (2021) found that cancer patients in end-of-life care wanted to receive the full truth about their disease rather than experience any distressing symptoms, were mentally aware in the last hour of life, felt meaningful in life, and could pass away with their loved ones around [17]. According to studies, half of admitted patients experience "loss of dignity" during futile care, with patients in intensive care units being at a higher risk [18].…”
Section: Introductionmentioning
confidence: 99%